Run away from war to find peace? - Barrera Rivera, Dan Abner (2020)
This article deals with the life story of Vicky, a Nicaraguan woman who fled her homeland escaping war.  The stories express personal and social situations pertaining to poverty, exploitation, immigration, aggression, family ruptures, resistance and the permanent fight for better living conditions in a new land.  The objective of the text is to present the narration of a foreign woman’s life from her own voice, from her point of view; here the “voice” of the researcher only appears to string together the facts of the central figure who lived them.  The narrated events reveal the existence of not only geographical borders, but also cultural, labor, social, educational and emotional limitations, which are often impassable, even if the same house or table is shared.  The document is an invitation to come closer and listen to the wisdom of an immigrant woman, who has made the streets her territory of struggle for the defense of her rights.